Influence of reproductive stages on gastrointestinal nematodes of sheep - YADAV, N K; MANDAL, AJOY; SHARMA, D K; ROUT, P K; ROY, R (The Indian Journal of Animal Sciences, 2011)
The study revealed that Muzaffarnagari ewes in lactating stages are more susceptible to parasitic infection as compared to dry and pregnant ewes. The significant variation in faecal egg count also exists between dry and pregnant animals. The lactating ewes had lower packed cell volume than dry and pregnant ewes during the infection stage. Â